TRADISI RITUAL SONGKRAN DI PATTANI, THAILAND SELATAN - Afnanee Panae (Sabda: Jurnal Kajian Kebudayaan, 2019)
Songkran ritual is a tradition performed every year, as a legacy from the ancestors of the Thai people. This ritual aims to welcome new year or new season. This paper aims to study the relationship between beliefs on Songkran day with myths and beliefs of the local community and the procession of rituals based on empirical facts of the local community. Pattani Province of Southern Thailand is a province of mixed religions, one of which is Buddhism. Pattani Province authority held the Songkran event on 13-15 April every year. Then Pattani Province was chosen as a place to collect data for research through literature studies to strengthen its expose to myths and rituals. Songkran ritual is performed as a form of belief to the joy and respect of parents. This ritual is carried out differently in each province and each place. Some of these ritual processions are carried out by families and neighborhoods only and some are done in general with the provincial authorities. This ritual basically has the same essence, which is an honorary ceremony for parents, going to temples, and taking part in drinking water.